Differential expression of five genes during sclerotium formation of Rhizoctonia solani - WANG Wei; YANG Hui; WANG Zhengyi; CHEN Weiliang (浙江大学学报. 农业与生命科学版)
Rhizoctonia solani is an important plant pathogenic fungus with a wide host range and worldwide distribution, and the sclerotia are the main source of infection for the diseases caused by this pathogen. The mechanism of formation and development of sclerotia of Rhizoctonia solan had been investigated by some researches, but they were mainly focused on the relationship between the sclerotium formation and the nutrition or environmental factors. There is still lack of the knowledge on the molecular basis of sclerotium formation of R. solani, and little is known about the sclerotium formation-related genes.Subtractive cDNA library of differentially expressed genes during the sclerotium formation of R. solani AG-1 IA (GD-118 strain) was constructed previously by using suppression subtractive hybridization (SSH) technique in our laboratory. The hyphal and sclerotium mRNA was used as the driver and tester, respectively. In the screening, some specific sclerotium formation-related gene fragments were identified and sequenced. According to the principle of hybrid SSH, the obtained gene fragments should be hyphal or sclerotium specific, but there were five gene fragments, we named them as A, B, C, E, F, respectively, detected both in hyphae and sclerotia. Bioinformatic analysis showed that these five gene fragments were correspondent with the genes putatively coding two-component response regulator, macrophage activating glycoprotein, extracellular elastinolytic metalloproteinase, Cyclophilin, and ER-derived vesicles protein ERV29. In this study, real-time quantitative PCR (QRT-PCR) was applied to further detect the gene expressions of A, B, C, E, F in different growing stages of R. solani by using the total RNAs as the templates and the 18S rRNA as the reference gene.The five gene expressions were determined by the QRT-PCR and calculated by the relative quantitative method (<inline-graphic xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="graphic/j.issn.1008-9209.2011.11.221-I001.jpg"/>). The results showed that: all of the five gene expressions decreased gradually from the initiation of sclerotium formation, but increased quickly at near maturation of sclerotia, then remained a constant level after maturation of sclerotia. Moreover, it was shown that these five gene expressions altered significantly among different growing stages of R. solani.According to the previous reports, the decrease of the expression of these five genes could repress the normal cell metabolism and result in the cell death, suggesting that the death of a large numbers of sclerotium outer cells during the sclerotium formation of R. solani may be associated with the expression levels of these five genes induced by external stresses. Obviously, complex metabolism and signal transduction pathways are involved in the cell death and the sclerotium formation, the detailed functions of these five genes in the signal transduction pathways leading to the sclerotium formation are still unclear and need to be studied deeply in the future.